Penile Amputation: Cosmetic and Functional Results. Issue 3 (17th April 2015) - Virasoro, Ramón; Tonkin, Jeremy B.; McCammon, Kurt A.; Jordan, Gerald H.
Abstract Introduction Penile amputation is a rare type of external genital trauma. It may arise from accidental trauma, assault or self‐inflicted mutilation. As with all trauma, initial management focuses on assessment and resuscitation of the patient. When available, hypothermic preservation of the detached penis should be undertaken. Aim This review serves to compile the current available information on etiology and management of penile amputation injuries, with focus on functional and cosmetic results. Main Outcome Measures Main outcome measures were penile cosmetics, viability, and sensation; urethral patency and graft survival, functionality. Methods A literature search using Medline, PubMed (U.S. National Library of Medicine and the National Institutes of Health), and abstracts from scientific meetings was performed from 1980–2013. Results Due to the rarity of penile amputation injuries, no randomized trials exist. Likewise, available published series on management of this condition are comprised of a small number of patients. Conclusions Penile amputation is rare but challenging. Current microreplantation procedures have a uniformly good result with a minimum number of post‐operative complications. When microreplantation cannot be performed, older corporal reattachment techniques may be offered. When phallic reconstruction is required, a microsurgical free forearm flap phalloplasty may be performed to restore the patient with an acceptable cosmetic and functional phallus. Virasoro R, Tonkin JB, McCammon KA, and Jordan GH. Penile amputation: Cosmetic and functional results. Sex Med Rev 2015;3:214–222.